Exploring the relationship between child-to-mother violence, types of aggression and family dynamics - Mackay, Kirstie-Louise (2017)
Relationships between child-to-mother violence (CMV) subtypes, aggression styles and level of family functioning were explored using a retrospective self-report design. Results from 86 participants revealed high frequencies of verbal and emotional CMV and low frequencies of financial and physical CMV. Regressions showed that high reactive and proactive aggression and dysfunctional family styles predicted verbal and emotional CMV. Whereas only high proactive aggression predicted financial and physical CMV. Psychological theories are considered to explain relationships between risk factors and CMV subtypes. Other relevant risk factors which interact with aggression styles and family functioning, such as mental health and substance misuse are discussed. Implications for preventative policies include collaborative multidisciplinary practice focusing on rehabilitation and tailored interventions for specific CMV and relevant risk factors.